Soil health and Fertility challenges and opportunities for sustainable production in the MENA region - Moussadek, Rachid; Lhomme, Patrick; Niane, Abdoul Aziz (2023)
MENA is facing tremendous challenges (food security, Climate Change, land degradation, biodiversity loss, water resource shortage and ecosystem sustainability…etc), These issues are closely related to soil functions that linking with biomass production, environmental and CC adaptation & mitigation. Wind erosion is the most common environmental problem in the region and accounts for y 60 % (135 M ha) of soil degradation. Erosion affects soil quality by removing the fertile top soils. Soil Salinity affected 11% of the NENA region